القضية الليبية في المحافل الدولية ودورها في تحقيق الاستقلال - الشديدأ.هناء محمود (Aljameai, 2025)
المستخلص: يتناول هذا البحث تطور القضية الليبية في المحافل الدولية منذ نهاية الحرب العالمية الثانية حتى إعلان الاستقلال سنة 1951م، مع التركيز على دور المؤتمرات الدولية في لندن وباريس، ثم انتقال الملف إلى الامم المتحدة، ويحلل البحث مساهمة الهيئات المنبثقة عن المنظمة الدولية ، مثل المجلس الاستشاري، ولجنة الواحد والعشرين، والجمعية الوطنية، في تمهيد الطريق لتشكيل الحكومة وإعلان الدستور والاستقلال، ويخلص إلى أن استقلال ليبيا كان نتاج تفاعل معقد بين الإرادة الوطنية والجهد الدولي. Abstract: This study examines the development of the Libyan question in international forums from the end of World War II to the declaration of independence in 1951. It focuses on the role of the London and Parish conferences and the subsequent transfer of the issue to the United Nations. The research analyzes the contribution of UN-sponsored bodies such as the Advisory Council, the Committee of Twenty-One, and the National Assembly I paving the way for the formation of the government, the proclamation of the constitution, and independence. The study concludes that Libyan independence was the result of a complex interaction between national will and international efforts.